2016
DOI: 10.1016/j.trf.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a simulated hearing loss on performance of an auditory memory task in driving

Abstract: Abstract:Hearing loss has been shown to exacerbate the effect of auditory distraction on driving 11 performance in older drivers. This study controlled for the potentially confounding factor of age-12 related cognitive decrements, by applying a simulated hearing loss in young, normally hearing removing capacity that could be used for other concurrent processes required for safe driving. 61The authors found that, compared to normally hearing participants, hearing impaired drivers An interesting, and unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Here, three difficulty levels of cognitive task were presented to drivers in a simulator study, and different measures of lane keeping performance were analyzed. In line with previous research (Cooper et al, 2013;Herbert et al, 2016;Jamson et al, 2005;), a lower SDLP was observed with concurrent cognitive load, in addition to an increase in steering reversal rate (at the 0.5 o level) and gaze concentration, with both measures showing a systematic change with increasing cognitive load.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Here, three difficulty levels of cognitive task were presented to drivers in a simulator study, and different measures of lane keeping performance were analyzed. In line with previous research (Cooper et al, 2013;Herbert et al, 2016;Jamson et al, 2005;), a lower SDLP was observed with concurrent cognitive load, in addition to an increase in steering reversal rate (at the 0.5 o level) and gaze concentration, with both measures showing a systematic change with increasing cognitive load.…”
Section: Discussionsupporting
confidence: 91%
“…SDLP during the 1-back task was only found to be lower than baseline (p=0.035). This finding shows that, in line with other studies, the cognitive load task causes a systematic reduction in lateral deviation, as measured by SDLP (Cooper et al, 2013;Herbert et al, 2016;Jamson et al, 2005;. SRR0.5 o : There was a significant main effect of task demands on SRR0.5 o (F(3, 93)=12.976, p<0.001, =0.295) , as shown in Fig.…”
Section: Driving Performancesupporting
confidence: 91%
See 1 more Smart Citation